The Influence Analysis of Marketing Mix on Customer Satisfaction “X” Books Store in the Faculty of Engineering, University Oo Sam Ratulangi Manado - Christian Nofeldy Supit; Tongam Sirait (Riviera Publishing, 2024)
Marketing mix or marketing mix is a set of marketing tools that companies use continuously to achieve their marketing goals in accordance with the market or target. The purpose of this study was to determine the effect of product, price, place, and promotion on customer satisfaction of “X” Books Store at the Faculty of Engineering, Sam Ratulangi University Manado. The type of research used in this research is quantitative with an explanatory research approach. Data collection was carried out by filling out questionnaires by respondents. The population of this study were students of the Department of Civil Engineering and Architecture totaling 1196, of which a sample of 93 students was taken based on the slovin calculation. Data analysis was carried out using Coefficient of Determination, and Ttest. Simultaneously using the Coefficient of Determination test, the 4P variables, namely product, price, place, and promotion, have an effect on customer satisfaction at the X “Books Store at the Faculty of Engineering, Sam Ratulangi University Manado with a percentage of 39.6%. Based on the Pasal test using the T test, the 4P variable hypothesis, namely product and promotion, does not have a significant effect on customer satisfaction with a percentage of 12% and 10.5%. Meanwhile, price and place have a significant effect on customer satisfaction with a percentage of 26.7% and 35.1% at the Faculty of Engineering, Sam Ratulangi University Manado. This research has implications for the importance of effective marketing mix management at “X” Books Store in order to increase customer satisfaction.